From emerging economies toward the emerging triad - Sebastian Dehnen; Jan H. van Dinther; Norbert Koubek (University of Wuppertal, Schumpeter School of Business and Economics, 2013)
In this article an entirely new structural approach called the 'Emerging Triad' is identified, which is dealing with the increasing regional, intra- and interregional integration of the emerging regions Latin America, Southeast Asia and sub-Saharan Africa. In this context the fast growing south-south cooperation's, specific transregional free trade agreements as well as foreign direct investments are identified as the main driver for this ongoing networking process. Due to their extended industrialization a similar development like the one of the BRIC countries can be anticipated for these regions in the upcoming years. Apart from the industrialization, the integration and interdependence of specific countries or even regions like Mercosur, SADC and ASEAN is going to be a relevant factor with respect to future market entry decisions of companies of the southern developing countries and a deeper market penetration of northern developed market multinational enterprises. Finally the new approach of the Emerging Triad and the northern triad with its developed nations are included into a double helix structure which stands for the tradeoff between the industrialized world and the emerging world.
urn:nbn:de:hbz:468-20131008-104717-3
Keywords: 330; Emerging triad; emerging markets; emerging market economies; BRIC; double helix structure; base of the pyramid; south-south cooperation; regional integration; Triad; FDI; trade